2020
DOI: 10.1098/rspb.2020.1671
|View full text |Cite|
|
Sign up to set email alerts
|

Captive-bred Atlantic salmon released into the wild have fewer offspring than wild-bred fish and decrease population productivity

Abstract: The release of captive-bred animals into the wild is commonly practised to restore or supplement wild populations but comes with a suite of ecological and genetic consequences. Vast numbers of hatchery-reared fish are released annually, ostensibly to restore/enhance wild populations or provide greater angling returns. While previous studies have shown that captive-bred fish perform poorly in the wild relative to wild-bred conspecifics, few have measured individual lifetime reproductive success (LRS) and how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 56 publications
1
37
1
Order By: Relevance
“…Genetic homogenization reduces one important aspect of intraspecific diversity. It further compromises individual and population fitness by disrupting local adaptations, at least in short to medium term, through the replacement of locally adapted alleles with non-adaptive ones, which is expected to reduce resilience to future environmental changes [ 11 , 21 , 24 ]. Thus, for salmon populations in the Baltic Sea, genetic homogenization has likely resulted in negative biological consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic homogenization reduces one important aspect of intraspecific diversity. It further compromises individual and population fitness by disrupting local adaptations, at least in short to medium term, through the replacement of locally adapted alleles with non-adaptive ones, which is expected to reduce resilience to future environmental changes [ 11 , 21 , 24 ]. Thus, for salmon populations in the Baltic Sea, genetic homogenization has likely resulted in negative biological consequences.…”
Section: Discussionmentioning
confidence: 99%
“…While in some cases such interventions may be beneficial for assisting threatened populations, a number of genetic conservation concerns have been identified (fitness reductions, reduced effective population size, reduced fitness of recipient populations, etc.) that depend on how artificial propagation and stocking is carried out [11,[21][22][23][24]. Several studies have also documented GH of native populations due to large-scale interbreeding with hatchery strains, including decreases in genetic structuring and isolation by distance (IBD) relationships [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Dotted line represents equal LRS between hatchery‐ and natural‐origin fish. Due to an outlier in O'Sullivan et al ( 2020 ) (see asterisk), the Atlantic Salmon figure (a) includes an inset representing the correct scale on the y‐axis. Araki, Ardren, et al ( 2007 ) results from the traditional hatchery programs with F1 fish originating from two hatchery‐origin parents and not adjusted for angling harvest.…”
Section: The Impact Of Hatchery Origin and Captive Rearing On Lifetime Reproductive Successmentioning
confidence: 99%
“…Across North America and Europe, implementation of captive-breeding programs is also used in combination with C&R to compensate decreasing recruitment on populations with abundance below their appropriate conservation threshold (DFO, 2008; MFFP, 2016; NASCO, 2017; ICES 2019). As for C&R, very few studies have documented patterns of reproductive success of captive-bred salmon (Milot et al 2012; O’Sullivan et al 2020). Previous research on captive-bred salmon demonstrated that minimizing time spent in captivity would alleviate unintentional domestication effect (Milot et al 2012).…”
Section: Introductionmentioning
confidence: 99%